INTERNALIZATION OF INDEPENDENT LEARNING VALUES IN ISLAMIC EDUCATION DURING COVID-19 AT MOJOSARI ELEMENTARY SCHOOL - Moh. Ainur Rokhim (Journal Of Islamic Education And Pesantren, 2022)
This study aims to analyze the internalization of Merdeka Belajar (Freedom to Learn) values in Islamic Religious Education (PAI) during the Covid-19 pandemic at SDN Kebondalem, Mojosari District, Mojokerto Regency. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal and PAI teachers, classroom observations, and documentation analysis of instructional plans and school policies. Data analysis was conducted through interactive stages of data reduction, data display, and conclusion drawing. The findings indicate that the internalization of Merdeka Belajar values was implemented through flexible, pressure-free learning focused on essential competencies and authentic assessment based on worship practices and value reflection. Teachers acted as facilitators and motivators, providing students with responsible learning autonomy adapted to their conditions during the pandemic. Collaboration between school and parents became a crucial supporting factor in sustaining the learning process. The study concludes that the Merdeka Belajar policy is not merely administrative but can be substantively implemented in PAI learning through humanistic, contextual, and character-oriented educational practices.